2012
DOI: 10.1007/s00337-012-0901-z
|View full text |Cite
|
Sign up to set email alerts
|

Das sensomotorische System und die Auswirkungen der Physiologie des Alterungsprozesses

Abstract: Diese Fortbildungseinheit steht Ihnen als e.CME und e.Tutorial in der Springer Medizin e.Akademie zur Verfügung. -e.CME: kostenfreie Teilnahme im Rahmen des jeweiligen Zeitschriftenabonnements -e.Tutorial: Teilnahme im Rahmen des e.Med-Abonnements ZertifizierungDiese Fortbildungseinheit ist mit 3 CMEPunkten zertifiziert von der Landesärzte-kammer Hessen und der Nord rheinischen Akademie für Ärztliche Fort-und Weiterbildung und damit auch für andere Ärzte-kammern anerkennungsfähig. Hinweis für Leser aus Österre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
4
1
Order By: Relevance
“…However, when considering the frontal and sagittal sway values of 21-30-year-old women (9.50 and 13 mm, respectively) [17] and 31-40-year-old women (8.17 mm/12 mm) [19], these values are lower than those in the present study, while those of 41-50-year-olds are larger and almost identical, respectively, with 13 mm in the frontal variation and 16.5 mm in the sagittal variation [20]. Consequently, the notion that the sway in joint weight is influenced by age can only be partially confirmed [4,5,38]. Regarding the weak positive correlations between age and the parameters sagittal and frontal body sway as well as the ellipse area and width, it can be concluded that the ability to balance slowly decreases over the course of life even without subjective, pathological information.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…However, when considering the frontal and sagittal sway values of 21-30-year-old women (9.50 and 13 mm, respectively) [17] and 31-40-year-old women (8.17 mm/12 mm) [19], these values are lower than those in the present study, while those of 41-50-year-olds are larger and almost identical, respectively, with 13 mm in the frontal variation and 16.5 mm in the sagittal variation [20]. Consequently, the notion that the sway in joint weight is influenced by age can only be partially confirmed [4,5,38]. Regarding the weak positive correlations between age and the parameters sagittal and frontal body sway as well as the ellipse area and width, it can be concluded that the ability to balance slowly decreases over the course of life even without subjective, pathological information.…”
Section: Discussioncontrasting
confidence: 84%
“…2022, 12, 9591 2 of 14 the visual system and/or the proprioceptive system, work together smoothly can the ability to balance be guaranteed at all. The systems involved can in turn influence different areas of the body, such as the musculoskeletal system, and at the same time be influenced by them (through endogenous or exogenous factors) [2][3][4][5]. Here, the musculoskeletal system neurophysiologically connects the muscles, fascia and nerves with each other [4,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since bone and muscle also interact closely chemically and metabolically, fat infiltration is also observed in age-related bone and muscle loss (sarcopenia) 57 . Furthermore, there is an age-related degenerative reduction in mitochondrial function as well as a reduction in the degree of interconnectedness of neurons at the neuronal level, which is also associated with a decrease in responsiveness as well as a reduction in processing speed with regard to motor function among other things [58][59][60][61] . Equivalent age-related changes in lumbar lodosis have not been demonstrated 55,62 .…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity (PA) is important for all body systems and general health as PA reduces the risk of obesity, osteoarthritis and the development of chronic pain [1] , [2] , [3] , [4] , [5] , [6] , [7] . Surrogate measures for PA include the number of steps per day (steps/day) and the amount of moderate to vigorous physical activity (MVPA).…”
Section: Introductionmentioning
confidence: 99%